Vaginal Estrogen Cream in Menopausal Women Using Pessary to Reduce Bacterial Vaginosis - Hakim, Surahman; Santoso, Budi Iman; Surya, Raymond; Kurniawan, Andrew Pratama (eJournal Kedokteran Indonesia, 2023)
Vaginal estrogen cream has widely been used for vaginal atrophy in menopausal women. However, the effectiveness in preventing bacterial vaginosis (BV) in women with pessary is limited. The study aims to evaluate the effectiveness of vaginal estrogen cream in preventing bacterial vaginosis in menopausal uterine prolapse women with a pessary. A literature search was conducted on PubMed®, Scopus®, and google scholar® before May 2022 using MeSH. Two investigators searched, extracted, and appraised the evidence. The studies were appraised using the Centre for Evidence-Based Medicine, University of Oxford, randomized controlled trial appraisal tools. There were two articles appropriate to the inclusion and exclusion criteria. Both studies were valid, important and applicable to our case. The relative risk of bacterial vaginosis after locally applied vaginal estrogen was 0.91-0.92, with a number needed to treat (NNT) 63.3-186.6. Estrogen vaginal cream did not reduce the risk of BV for menopausal women with pessary in the short term; however, BV incidence is reduced in the longer term.